Discrimination Of Women In Khaled Hosseini's A Thousand Splendid Suns Novel (2007): A Sociological Approach - Mahanani, Rustamia Tri; , Drs. Abdillah Nugroho, M. Hum; , Siti Fatimah, S. Pd, M. Hum (2014)
This study is aimed to show the Discrimination of Women in Afghanistan when conflict in Afghanistan a long of decade 1970 until 2000 in Khaled Hosseini A Thousand Splendid Suns Novel by using sociological approach. It is done by establishing two objectives: the first is analyzing the novel based on structural elements of the fiction and second is analyzing the novel based on the sociological approach. This research is qualitative research. Type of the data study is quotation and story taken from two data sources: primary and secondary. The primary data source is A Thousand Splendid Suns novel by Khaled Hosseini released in 2007. While the secondary data sources are other materials taken from books and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. Firstly, based on the structural analysis of each elements, it shows that the character and characterization, setting, plot, point of view, style, and theme so it influential of discrimination from action friction between men and women and causes of injustice right in society . Secondly, based on the sociological analysis, there is a close relationship between the story of novel and the reality condition of women in Afghanistan who get discrimination when conflict a long of decade 1970 until 2000.